Isolation and functional characterization Of bacterial strain b1 from erode region,Tamilnadu, india - VIJAYANANDINI GOVINDAN,; K VIJAYA RAMESH, (International Journal of Pharma and Bio Sciences, 2018)
Azo dyes are recalcitrant to degradation due to high degree of chemical complexity, biological and photochemical stability. Disposal of treated dye effluent by physical and chemical methods are not economical. Incomplete removal of azo dyes, their toxic byproducts, results in significant amount of sludge accumulation, leading to secondary pollution problems. However, microbial and enzymatic decolouration is a cost effective process. On this basis, azodye effluent and soil samples from the textile dyes affected region were collected and they were screened for the presence of azo dye (Methylene blue and Congo red) degrading bacteria and fungi by direct plating and enrichment isolation. Enrichment cultures showed promising azo dye degrading strains. Among the efficient cultures, two bacterial cultures namely strain B1(Bacillus subtilis),strain VGVR-06(Pseudomonas aeruginosa) and two fungal cultures namely strain AF-1(Aspergillus flavus),strain AN-1(Aspergillus niger) were further phylogenetically identified. Among the above, strain B1 (Bacillus subtilis) was promising azoreductase enzyme producer. Further the presence of the enzyme was confirmed through azoreductase enzyme assay and by sequencing and amplifying the azoreductase gene from those bacteria.